2021
DOI: 10.1097/dcr.0000000000001823
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up, Patient Satisfaction, and Quality of Life for Patients With Kock’s Continent Ileostomy

Abstract: BACKGROUND: Continent ileostomy is a solution for patients after proctocolectomy. OBJECTIVE: The aim of this study was to assess the long-term complications and failure rate alongside patient satisfaction, function, and quality of life for patients with a continent ileostomy. DESIGN: This was a retrospective, descriptive cross-sectional study. SETTINGS: All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Similarly, Risto et al found that age matched Swedish controls had similar SF‐36 scores to those with a Kock pouch. Risto et al reported 84% of patients were satisfied and 82% would choose a Kock pouch again [19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Risto et al found that age matched Swedish controls had similar SF‐36 scores to those with a Kock pouch. Risto et al reported 84% of patients were satisfied and 82% would choose a Kock pouch again [19].…”
Section: Resultsmentioning
confidence: 99%
“…A total of six studies published in seven articles looked at quality of life after a Kock pouch. Litle et al, Risto et al, and Berndtsson et al used the Short Form 36 Health Survey (SF‐36) [9, 11, 19] and Hoekstra et al used the SF‐36 with the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Colorectal Cancer Module (EORTC QLC‐CR38) [15]. Castillo et al used a non‐validated quality of life questionnaire [14] and Lian et al used the Cleveland Global Quality of Life questionnaire (CGQL) [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the authors view, not enough attention has been paid to the pouch itself and the influence of the underlying diseases. Thus, the discussion is mostly triggered by technical considerations only, albeit CD has largely been considered an unspecified risk factor for all complications and pouch failures, but based on limited and biased data [19][20][21]. The data presented here focusses exclusively on the analysis of all patients requiring revisions and is a unique large data set with (very) long follow-up.…”
Section: Discussionmentioning
confidence: 99%